Natural polymers: Preparation, applications and benefits (Eurasian Journal of Research, Development and Innovation, 2024)
Natural polymers are the major components of all living matter; cheap, available and most importantly eco-friendly . They are widely used in many fields. This research will cover a few types of natural polymers. How can we obtain them ,their application ,structure and the different way they can be a part of our daily lives without being harmful to our health and environment.